Effectiveness of community of inquiry based online course: Cognitive, social and teaching presence - Seda Aktı Aslan; Yiğit Emrah Turgut (Journal of Pedagogical Research, 2021)
This quasi-experimental study aimed to examine students’ community of inquiry perceptions through online learning activities designed based on the community of inquiry model. The participants of the study consisted of 81 freshmen enrolled in two different departments of a Turkish state university. The process for the experimental procedure was carried out as part of the Information Technologies course. Due to the COVID-19 pandemic, the research process was carried out with synchronous distance education. While the control group received instruction through direct instruction and question/answer technique, the experimental group received instruction based on the community of inquiry model. For data collection, a demographic information form and the community of inquiry scale were administered. According to the results, students in the experimental group had significantly higher scores in terms of cognitive and teaching presence compared with the students in the control group. On the other hand, no significant difference was observed between the groups in terms of their social presence scores. Overall, the students in the experimental group had higher community of inquiry score than the students in the control group.